Development and Psychometric Testing of Perfectionism Inventory to Assess Perfectionism and Academic Stress in University Students: A Cross-Sectional Multi-Centre Study - Michela Piredda; Alessio Lo Cascio; Anna Marchetti; Laura Campanozzi; Paolo Pellegrino; Marina Mondo; Giorgia Petrucci; Roberto Latina; Maddalena De Maria; Rosaria Alvaro; Maria Grazia De Marinis (European Journal of Investigation in Health, Psychology and Education, 2025)
Background: Perfectionism is a growing concern among university students, who face high expectations, demanding workloads, and complex academic tasks. These pressures often lead to stress, negatively impacting performance, well-being, and career trajectories. Existing measures of perfectionism and related stress lack focus on their causes and relevance to students. Methods: This study developed and psychometrically tested an inventory assessing the causes (ROOTS), manifestations (MPS-R), and stress (IPSS-R) related to perfectionism. A multicenter cross-sectional online survey was conducted across multiple Italian universities with 469 students. The ROOTS tool was developed, and the MPS and IPSS were adapted following established guidelines. Content validity was examined, and pilot testing was performed. Confirmatory factor analyses tested three-factor models with a second-order factor for each instrument. Construct validity and reliability were also assessed. Results: The ROOTS, MPS-R, and IPSS-R demonstrated strong structural and construct validity, with acceptable reliability. Significant correlations highlighted the interconnectedness of perfectionism’s causes, manifestations, and stress. Conclusions: The Perfectionism Inventory offers a comprehensive tool for identifying causes, manifestations, and consequences of perfectionism in university students. It can help educators and policymakers develop strategies to mitigate its impact on mental health and academic success. Future research should explore its applicability in other populations.